2012
DOI: 10.1002/jez.1727
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of an Immature Vestibular System to Altered Gravity

Abstract: Stimulus deprivation or stimulus augmentation can induce long-lasting modifications to sensory and motor systems. If deprivation is effective only during a limited period of life this phase is called "critical period." A critical period was described for the development of the roll-induced vestibuloocular reflex (rVOR) of Xenopus laevis using spaceflights. Spaceflight durations and basic conditions of Xenopus' development did not make it possible to answer the question whether exposure of the immature vestibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In both species, rVOR development is retarded during early periods of life if the animals are reared for several days or permanently in complete darkness (Sebastian et al, 1996;2001). In Pleurodeles, the rVOR cannot be elicited until 15 days after fertilization (stage 37); thereafter, its amplitude and gain increase steadily and reach a saturation level of about α = 20° at stage 48 (Gabriel et al, 2012) (Fig. 16.1).…”
Section: Developmental Characteristics Of Vestibular Functionmentioning
confidence: 93%
See 3 more Smart Citations
“…In both species, rVOR development is retarded during early periods of life if the animals are reared for several days or permanently in complete darkness (Sebastian et al, 1996;2001). In Pleurodeles, the rVOR cannot be elicited until 15 days after fertilization (stage 37); thereafter, its amplitude and gain increase steadily and reach a saturation level of about α = 20° at stage 48 (Gabriel et al, 2012) (Fig. 16.1).…”
Section: Developmental Characteristics Of Vestibular Functionmentioning
confidence: 93%
“…Because during the post-3g period animals were kept in regular light-dark cycles, the accelerated 1g readaptation in the low stimulation range might be caused by the normally higher light response in fish (dorsal light response) compared to Xenopus . 4) The salamander Pleurodeles differed from these normalization dynamics after hypergravity exposure because the larvae developed a delayed vestibular sensitization by 3g as shown by the augmented vestibulo-ocular reflex four weeks after termination of 3g exposure (Gabriel et al, 2012).…”
Section: ) Lordoticmentioning
confidence: 99%
See 2 more Smart Citations
“…This curve was used to calculate the rVOR amplitude, which is the maximal peak-to-peak movement of the eyes during a 360deg lateral roll. Previous studies in Xenopus laevis, young fish (Oreochromis mossambicus) and salamander larvae (Pleurodeles waltl) have shown that the rVOR amplitude is a sensitive indicator to describe (1) modifications of the rVOR during development (Horn et al, 1986a;Sebastian and Horn, 1999;Gabriel et al, 2012), (2) the susceptibility to changes within the vestibuloocular system induced by vestibular lesions (Horn et al, 1986b), (3) the extent of vestibular plasticity after such lesions (Rayer and Horn, 1986) and (4) the impact of altered gravitational conditions on vestibular function (Horn 2006;Sebastian et al, 2001;Horn and Gabriel, 2011;Gabriel et al, 2012). The rVOR amplitude was determined by the angular difference between the mean of eye angles recorded for roll angles between 60deg to 120deg and 240deg to 300deg, respectively (cf.…”
Section: Recordings Of the Rvormentioning
confidence: 99%